Hubungan Layanan Bimbingan Konseling dengan Prestasi Belajar Siswa Sekolah Menengah Pertama Islam Terpadu (SMPIT) Bina Insan Cendekia - Putri, Galuh Andina (Al Musyrif: Jurnal Bimbingan dan Konseling Islam, 2022)
Even though it is a top school and has a myriad of achievements, it is undeniable that there are still students at SMPIT Bina Insan Cendekia who have problems with learning enthusiasm or concentration in learning. So this study aims to determine the relationship between counseling guidance and learning achievement at SMPIT Bina Insan Cendekia. This research is a quantitative study with a population of 339 students. The results of this study indicate that guidance and counseling services have an impact on student learning outcomes at SMPIT Bina Insan Cendekia, Pasuruan City.